Mitochondrial function and nitric oxide metabolism are modified by enalapril in rat kidney - Piotrkowski, Barbara (2007)
The renal and cardiac benefits of renin-angiotensin system (RAS) inhibition in hypertension exceed those attributable to blood pressure reduction, and seem to involve mitochondrial function changes. To investigate whether mitochondrial changes associated with RAS inhibition are related to changes in nitric oxide (NO) metabolism, four groups of male Wistar rats were treated during 2 wk with a RAS inhibitor, enalapril (10 mg·kg-1·day-1; Enal), or a NO synthase (NOS) inhibitor, Nω-nitro-L-arginine methyl ester (L-NAME) (1 mg·kg-1·day-1), or both (Enal+L-NAME), or were untreated (control). Blood pressure and body weight were lower in Enal than in control. Electron transfer through complexes I to III and cytochrome oxidase activity were significantly lower, and uncoupling protein-2 content was significantly higher in kidney mitochondria isolated from Enal than in those from control. All of these changes were prevented by L-NAME cotreatment and were accompanied by a higher production/bioavailability of kidney NO. L-NAME abolished mitochondrial NOS activity but failed to inhibit extra-mitochondrial kidney NOS, underscoring the relevance of mitochondrial NO in those effects of enalapril that were suppressed by L-NAME cotreatment. In Enal, kidney mitochondria H2O2 production rate and MnSOD activity were significantly lower than in control, and these effects were not prevented by L-NAME cotreatment. These findings may clarify the role of NO in the interactions between RAS and mitochondrial metabolism and can help to unravel the mechanisms involved in renal protection by RAS inhibitors. Copyright © 2007 the American Physiological Society.